Experimental Behaviour of Sandwich Panels Using Copper Slag Mortar - Lavanya Prabha.Sa, Dr; Neelamegam, Dr; Sri.R, Vinodhini (International Journal of Engineering and Technology, 2018)
This paper presents the study to investigate the viability of using copper slag as fine aggregate in cement mortar. Two series of cement mortar mixtures were prepared with different proportion of copper slag at different workability. In the first series, various proportions of copper slag is substituted for sand ranging from 0% to 100% with constant workability. Second series consists of fully replaced copper slag for sand in the cement mortar, which was achieved by maintaining the same workability as that of the control mortar mixture from first series and a control mixture for this new workability with sand as fine aggregate. The strength of twelve trial cement mortar mixtures were tested. The results indicate high compressive strength upto 50% replacement of copper slag, after that the compressive strength decreases with increase in copper slag percentage in cement mortar. The copper slag content in the mortar adversely affected the compressive strength of the mortar mixtures as 4.2% and 21.1% improvement in the compressive strength of the cement mortar for 50% replacement compared and 100% replacement compared with the control mortar mixtures. The density of cement mortar increases with increase in copper slag. From these trial mixtures two optimized mixtures were selected and were used to cast the sandwich panels. This panels were tested for flexural behaviour and axial load compression behaviour. The behavior of sandwich panels were simulated using ANSYS and the results were compared with experimental results.Â Â Â